Fashion Photography in Public Spaces - Méndez Moreno, Juan Pablo Méndez Moreno (situArte, 2021)
The study deals with fashion photography as an object of communication that has been used as a complement to ideological exposure in public spaces. The work focuses mainly on the proposals of Heidegger (2012) and Dubois (1990) on the implications of photography in physical space. This phenomenon is currently involved in a virtuality through the internet. These images seek consumer fanaticism and refer to the ideal self; they encourage the consumption of products and the ways of conceiving ethnicity, clothing, identity and body, reducing the latter to a two-dimensional plastic form. The research contributes to the growing area of the use of images in concurrency sites, sensory marketing and the representation of the body through it; it encourages reflective postures in relation to messages in the mass media.